Literature Inside The Tree: Teaching The Tempest in The Bahamas Department of Correctional Services Facility at Fox Hill - Smith, Philip (International Journal of Bahamian Studies, 2018)
This paper seeks to assess the utility of a Shakespeare Behind Bars programme at The Bahamas Department of Correctional Services Facility at Fox Hill. It argues that, consistent with Kidd and Castano’s (2013) findings, students engaged in literary analysis practice ”Theory of Mind” and cultivate the means to narrate their own history. Students, we found, refracted their life experience to the play, reading the text in terms of social ostracism, the influences of their life course, imprisonment, and reform. They tended to relate most closely to those characters whom they saw as having learned from incarceration and who were committed to a new life course. Their insights provided a perspective on the play to which we instructors would not otherwise have had access.